2010
DOI: 10.1016/j.jcin.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Treatment of Microvascular Obstruction-Related Myocardial Injury and Coronary No-Reflow Following Percutaneous Coronary Intervention

Abstract: Microvascular obstruction (MVO) commonly occurs following percutaneous coronary interventions (PCI), may lead to myocardial injury, and is an independent predictor of adverse outcome. Severe MVO may manifest angiographically as reduced flow in the patent upstream epicardial arteries, a situation that is termed "no-reflow." Microvascular obstruction can be broadly categorized according to the duration of myocardial ischemia preceding PCI. In "interventional MVO" (e.g., elective PCI), obstruction typically invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(124 citation statements)
references
References 81 publications
1
118
1
4
Order By: Relevance
“…25) Bahrmann, et al demonstrated that a large amount of embolic particles could reduce the post-PCI CFR. 10) In the present study, we excluded patients with side-branch occlusion after PCI, which could lead to low post-PCI CFR.…”
Section: Discussionmentioning
confidence: 99%
“…25) Bahrmann, et al demonstrated that a large amount of embolic particles could reduce the post-PCI CFR. 10) In the present study, we excluded patients with side-branch occlusion after PCI, which could lead to low post-PCI CFR.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,10 Various approaches have been explored to reverse MVO in clinical trials, but their efficacy is unclear. 26 MVO regions are composed primarily of necrotic tissue; therefore, reversal of MVO is not expected to rescue viable myocardium but instead to optimize healing and achieve better long-term outcomes. The present results showed that the impaired infiltration of monocytes/macrophages in MVO regions was associated with worse functional outcomes in rats.…”
Section: Monocyte Recruitment In Mvo Areas: a Potential Diagnostic Mamentioning
confidence: 99%
“…29,30 The poor prognosis with no-reflow is due to larger infarct sizes and reduced systolic function left ventricule. 30 The clinical trials tested a number of treatment strategies for no-reflow have been conflicting and there is no definitive treatment of no-reflow once it has occurred.…”
Section: -20mentioning
confidence: 99%
“…29,30 The poor prognosis with no-reflow is due to larger infarct sizes and reduced systolic function left ventricule. 30 The clinical trials tested a number of treatment strategies for no-reflow have been conflicting and there is no definitive treatment of no-reflow once it has occurred. [31][32][33][34][35] In the absence of an effective treatment strategy, it is crucial to prevent no- reflow by knowing the predictors or risk factors of no-reflow.…”
Section: -20mentioning
confidence: 99%